Guided Inquiry Sebagai Strategi Efektif Dalam Meningkatkan Kemampuan Berpikir Kritis Siswa Pada Pembelajaran IPAS Kelas IV SD Negeri 131/II SKB - Putri, Silvia Ristia; Subhanadri, Subhanadri; Apdoludin, Apdoludin (Master of Pedagogy and Elementary School Learning, 2025)
This research is motivated by the low critical thinking skills of grade IV D students of SDN 131/II SKB. This study aims to improve the learning process and critical thinking skills of students using the Guided Inquiry learning model. The research method used is Classroom Action Research (CAR). The research was conducted in two cycles, each cycle consisting of planning, implementation, observation, and reflection. The subjects of the research were 35 students of class IV D. The object of the research is the process and critical thinking skills of students. The data collection techniques used are observation and test techniques. The data collection instruments used observation sheets, critical thinking ability test sheets for students and documentation. Analysis of research data used qualitative and quantitative data analysis. The results of the study can be seen that the learning process and critical thinking skills of students have increased, this is evidenced by the assessment of teacher and student performance and the results of critical thinking ability tests. In the assessment of teacher performance in cycle I meeting I was 84% and in cycle I meeting II increased to 88% so that the percentage of teacher performance in cycle I 86% can be considered very good. While in cycle II meeting I increased to 91% and in meeting II increased to 96% so that the percentage of teacher performance in cycle II was 93.5%. In addition, the results of the assessment of the student learning process in each cycle per meeting increased, namely in cycle I meeting I from 72.06% to meeting II 76.57% there was an increase of 6.26%. Furthermore, cycle I meeting II to cycle II meeting I from a value of 76.57% to 81.84% there was an increase of 6.88%. Then from cycle II meeting I 81.84% to cycle II meeting II 89.16% there was a significant increase reaching 8.94%. And students' critical thinking skills also increased during the pre-cycle reaching a value of 45.71% in the (less critical) category. In cycle I it increased to 71.43% in the (critical) category and in cycle II it increased significantly to 91.43% in the (very critical) category, thus achieving the target indicator of critical thinking skills success, which is 65%.